2000
DOI: 10.1029/2000ja900057
|View full text |Cite
|
Sign up to set email alerts
|

Small substorms: Solar wind input and magnetotail dynamics

Abstract: We investigated properties of 43 small magnetospheric substorms. Their general signatures were found to be consistent with the so-called contracted oval or northern Bz substorms. Small but clear pressure changes in the tail corresponding to growth and expansion phases detected in about a half of cases testify that these substorms follow the same loading-unloading scheme as the larger ones. However, rate of the solar wind energy accumulation in the magnetosphere was low due to azimuthal IMF orientation with dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 25 publications
2
49
1
Order By: Relevance
“…This finding is in agreement with the level of fluctuations in the solar wind (the standard deviation of the solar wind parameters) being much lower for the SMCs than for any other event type (Partamies et al, 2009). Without obvious particle injections at the onset, the isolated substorms may seem like what was described as small substorms during a contracted auroral oval by Petrukovich et al (2000) and Lui et al (1976). The average AL peak of −200 nT for our substorm events is in the range of small substorms by Petrukovich et al (2000).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This finding is in agreement with the level of fluctuations in the solar wind (the standard deviation of the solar wind parameters) being much lower for the SMCs than for any other event type (Partamies et al, 2009). Without obvious particle injections at the onset, the isolated substorms may seem like what was described as small substorms during a contracted auroral oval by Petrukovich et al (2000) and Lui et al (1976). The average AL peak of −200 nT for our substorm events is in the range of small substorms by Petrukovich et al (2000).…”
Section: Discussionmentioning
confidence: 95%
“…Without obvious particle injections at the onset, the isolated substorms may seem like what was described as small substorms during a contracted auroral oval by Petrukovich et al (2000) and Lui et al (1976). The average AL peak of −200 nT for our substorm events is in the range of small substorms by Petrukovich et al (2000). However, the other criteria for small substorms are not fulfilled by our event group: instead of the PC index staying below unity, we found peak values of 1.5, and instead of the substorms occurring at and north of Bear Island station (71.45 • MLAT) the mean latitude of the onset latitude for our data set is 66.5 • MLAT.…”
Section: Discussionmentioning
confidence: 99%
“…Substorms can occur for southward as well as northward IMF [Akasofu et al, 1973;Lui et al, 1976;Lee et al, 2010]. However, substorms are much weaker for northward than southward IMF conditions [Petrukovich et al, 2000;Kullen and Karlsson, 2004;Pulkkinen et al, 2007;Peng et al, 2013]. Recent simulation result showed that the Earth's magnetosphere system may be more strongly driven during southward IMF [Tsurutani and Gonzalez, 1995;Lu et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the magnetotail field as the main reservoir of energy dissipated during substorms have been questioned by Pulkkinen et al [2006]. Several examples of substorm onsets, not preceded by a pressure or magnetic flux increase in the magnetotail, have been presented [Petrukovich et al, 2000;Yahnin et al, 1994Yahnin et al, , 2001DeJong et al, 2008]. This has also been statistically confirmed by Dmitrieva et al [2004] who noticed that ∼1/3 out of 145 isolated substorm events in the midtail studied did not show any total pressure growth before unloading, whereas a classical growth phase was observed only in the other 1/3 of events (the remaining 1/3 showed a mixed behavior).…”
Section: Introductionmentioning
confidence: 99%